Student interest development in course-based undergraduate research experiences (CUREs): a longitudinal case study analysis - Bennie, Juliette; Zhang, Kathy; Yeh, Phoebe; Gill, Julia C.; Crowley, Lia; Bauer, Melanie; Graham, Mark J. (Frontiers in Education, 2025)
IntroductionStudent participation in course-based undergraduate research experiences (CUREs) leads to improved academic performance and increased intent to persist in STEM, especially when compared to traditional lecture courses with standard assignments. Despite the benefits of CUREs, less is known about a student's week-by-week experiences in CUREs and how specific CURE course features contribute to student development toward learning outcomes. Previous research found that students' levels of frustration in CURE courses moderates the relationship between their feelings of challenge and interest. This study provides more context for how specific CURE course activities moderate students' week-to-week experiences of interest-challenge-frustration dynamics.MethodsThis longitudinal study develops and analyzes detailed case studies for seven students by: (1) analyzing surveys distributed at seven time points throughout a semester in a CURE, (2) conducting interviews with students during the summer following their CURE to gain qualitative insights to survey data, and (3) analyzing surveys distributed to students over a year after their CURE.Results and DiscussionFindings highlight a number of factors that are important for student interest in CURE courses. These include peer and professor interactions, student autonomy, relevance of course activities to personal goals, and development of research skills. Findings also suggest that students' interest in CUREs can promote sustained content knowledge, project ownership, science identity, and confidence. To better support student interest in CUREs, instructors should continue to promote student collaboration, offer mentorship, and encourage students to see the relevance of CURE tasks.